Mass spectrometry quantifies protein interactions--from molecular chaperones to membrane porins. - Hopper, J; Robinson, C (Wiley, 2014)
Proteins possess an intimate relationship between their structure and function, with folded protein structures generating recognition motifs for the binding of ligands and other proteins. Mass spectrometry (MS) can provide information on a number of levels of protein structure, from the primary amino acid sequence to its three-dimensional fold and quaternary interactions. Given that MS is a gas-phase technique, with its foundations in analytical chemistry, it is perhaps counter-intuitive to use it to study the structure and non-covalent interactions of proteins that form in solution. Herein we show, however, that MS can go beyond simply preserving protein interactions in the gas phase by providing new insight into dynamic interaction networks, dissociation mechanisms, and the cooperativity of ligand binding. We consider potential pitfalls in data interpretation and place particular emphasis on recent studies that revealed quantitative information about dynamic protein interactions, in both soluble and membrane-embedded assemblies.